1390. Pharmacokinetic-Pharmacodynamic (PK-PD) Target Attainment Analyses to Support Rezafungin (RZF) Dose Selection in Treatment of Candida. (26th November 2018) - Lakota, Elizabeth A; Ganesan, Harish; Flanagan, Shawn; Ong, Voon; Sandison, Taylor; Bhavnani, Sujata M; Rubino, Christopher M; Ambrose, Paul G
Abstract: Background: RZF is a novel antifungal of the echinocandin class with distinctive pharmacokinetics that support weekly dosing intervals. RZF is being developed for the treatment of candidemia and invasive candidiasis (IC) and the prevention of invasive fungal infections. A previously developed population PK model based on Phase 1 intravenous (IV) data [AAC 2018; e02603–17] was refined using IV data from additional Phase 1 and Phase 2 (STRIVE) studies. Methods: Data from the two Phase 1 studies used previously to develop the model were pooled with data from an additional Phase 1 study and the STRIVE trial in patients with candidemia and/or IC. The population PK model was refined using NONMEM Version 7.2. The ability of covariates such as body size, age, sex, albumin, markers of liver and renal function, and infection status to explain a portion of the interindividual variability on select PK parameters was explored using stepwise forward selection ( α = 0.01) and backward elimination ( α = 0.001). The final model was externally validated by comparing model-based predictions to observed data from STRIVE, which were not available during model development. Results: The final population PK model was a linear, four-compartment model with zero order IV input. Albumin was the most important predictor of the interindividual variability in RZF PK as significant relationships were found between serum albumin concentration and clearance, volume of the central compartment, volume of peripheral compartment 1, and volume of peripheral compartment 2. Additional relationships were found between PK parameters and sex, body weight, and infection status. The model provided precise and unbiased fits to the observed data (Figure 1). Differences in predicted median AUC across a wide range of covariate values were modest (Figure 2). The final model was also able to predict the central tendency and variability in RZF concentration–time data from patients with candidemia and/or IC not included in the model development (Figure 3). Conclusion: A population PK model describing RZF PK in healthy subjects and patients with candidemia and/or IC was successfully developed. This model was utilized for subsequent PK-PD target attainment analyses to support dose selection for RZF. Disclosures: E. A. Lakota, Cidara Therapeutics: Research Contractor, Research support. H. Ganesan, Cidara Therapeutics: Research Contractor, Research support. S. Flanagan, Cidara Therapeutics: Employee and Shareholder, Salary and stock options. V. Ong, Cidara Therapeutics: Employee and Shareholder, Salary and Stock options. T. Sandison, Cidara Therapeutics: Employee and Shareholder, Salary and Stock options. S. M. Bhavnani, Cidara Therapeutics: Research Contractor, Research support. C. M. Rubino, Cidara Therapeutics: Research Contractor, Research support. P. G. Ambrose, Cidara Therapeutics: Research Contractor, Research support.